STRATEGI PERUSAHAAN LOKAL MENGHADAPI PERSAINGAN MASYARAKAT EKONOMI ASEAN (MEA) - Johanes Jenu Widjaja Tandjung (Politeknik Ubaya, 2017)
Business competition in Indonesia has entered a new chapter, immediately upon the ASEAN Economic Community establishment in 2015. Since then, the domestic market has been penetrated by foreign competitors, particularly from ASEAN member states, China, and South Korea. It is inevitable that the regional competition impinges local business lines. Therefore, these enterprises must initiate “glocally” marketing strategy - a global approach with a local taste that attracts local prospects.